Analysis of the Role of Export-Import in Indonesia: The Positive Impact of Export-Import Activities on Indonesia's Economic Growth - Dhea Kristina Manik; Grace Renita P. Sibuea; Desy Sabriana Br Sinuhaji; Berkat Kristina H. Lumbanraja; Sri Nova Tresia Sihotang; Feronica Simanjorang (Experimental Student Experiences, 2024)
This study aims to determine the role of import and export on Indonesia's economic growth. A country's economy cannot be separated from global economic conditions. The economy of each country is strongly influenced by its economic relations with other countries. Thus, competitiveness is an important component in the Indonesian economy. This research uses a literature review or literature review. Exports in the short term show that the export variable has no significant effect on economic growth in the short term. While in the long term, the export variable has a significant effect on economic growth in Indonesia. Furthermore, the import variable does not have a significant effect on economic growth in the short term, but will be very influential in the long term. This research is expected to provide insight and knowledge on the export and import nature of economic growth in Indonesia.